Designing and Validation of a Living Standards Questionnaire in Tehran's Elderly Community - Mina Jahanpour; Seyed Hossein Mohaqeqi Kamal; Samaneh Hosseinzadeh; Homeira Sajjadi; Mehdi Basakha (University of Social Welfare & Rehabilitation Sciences, 2019)
Objectives Considering the importance of assessing living standards in society, the present study aimed to design a living standards questionnaire. We also assessed the validity and reliability of the developed questionnaire in the Iranian elderly population. Methods & Materials This was a methodological study. Initially, by reviewing the relevant theoretical and empirical bases like questionnaires in English, 45 questions were selected for developing living standards questionnaire. Then, the content and face validity of the questionnaire were evaluated using the comments of 10 university experts. Moreover, its structural validity (factor analysis by varimax rotation) was investigated. After determining the validity of the scale, the questionnaire was completed by 150 elderly people aged ≥60 years. The internal consistency reliability of it was investigated using Cronbach's alpha coefficient and split-half reliability. The obtained data were analyzed by SPSS. Results The Mean±SD age of samples was 63.74±2.99 years. The content validity of the questionnaire was equal to 0.85. In the structural validity assessment, the Kaiser-Meyer-Olkin (KMO) value was obtained as 0.853, and three factors (living facility, housing situation, and household expenditures) together explained 56.8% of the total variances. The Cronbach's alpha coefficient was equal to 0.859 for the total scale and the Gutmann split-half coefficient was calculated as 0.859. Conclusion The obtained results revealed that the living standards questionnaire was a valid and reliable scale in Tehran's elderly population.